Predicting natural language descriptions of mono-molecular odorants - E. Darío Gutiérrez; Amit Dhurandhar; Andreas Keller; Pablo Meyer; Guillermo A. Cecchi (Nature Communications, 2018)
It is now possible to predict what a chemical smells like based on its chemical structure, however to date, this has only been done for a small number of odor descriptors. Here, using natural-language semantic representations, the authors demonstrate prediction of a much wider range of descriptors.